Implementasi Total Quality Management (TQM) di SD Al-Hikmah Surabaya - Rahmah, Ulfatur (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to analyze and explain the key factors contributing on successful implementation of total quality management in Al-Hikmah Primary School of Surabaya. The sustainability of total quality management in Al-Hikmah Elementary School is proven by the increasing number of students’ enrolment which exceeded the fixed quota; the high level of teachers and students achievement; as well as the big number of competitive graduates. Using qualitative descriptive approach, this research finds that successful implementation of total quality management is highly dependent on top-down leadership system of the school, effective communication among stakeholders, the properly measured reward and punishment to students, and the continous internal and external assessment of educational quality management.